ANALYSIS OF THE ACCOUNTING SYSTEM FOR CASH RECEIPTS AT THE FORMER PERTAMINA WORK COOPERATIVE (PURNAMA) MEDAN BRANCH - Rayhan Ananda; Debora Tambunan; Arsyaf Tampubolon; Dewi Rafiah Pakpahan; Dompak Pasaribu; Frans Gideon Sinuhaji (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
This study aims to determine the application of the accounting system for cash receipts on the sale of 3Kg LPG gas at the Medan branch of the purna karya pertamina cooperative. Data collection methods used in this research are observation, documentation, interviews. Cash is the most liquid asset that a company can have because cash is a type of current asset where every company transaction both inside and outside the company can affect cash. This research was conducted by obtaining qualitative data. Qualitative data in this study was obtained by conducting direct research to the leadership of Pertamina Purna Karya Cooperative Medan Branch. Purna Karya Pertamina Cooperative has several types of cash receipts, namely Cash Receipts from LPG Gas Sales and Cash Receipts from Transfer Fees. The results of this study indicate that the accounting system for cash receipts at the purna karya pertamina cooperative for the sale of LPG gas can provide accurate related information.